2006
DOI: 10.1073/pnas.0606850103
|View full text |Cite
|
Sign up to set email alerts
|

The von Hippel–Lindau tumor suppressor gene product represses oncogenic β-catenin signaling in renal carcinoma cells

Abstract: Loss of vonc-Met ͉ hepatocyte growth factor ͉ renal cell carcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 58 publications
2
75
0
2
Order By: Relevance
“…It nonetheless is intriguing that MET, CDK6, and MAP2K1 have been linked previously to kidney cancer biology. Germline MET mutations cause papillary renal carcinoma, and there is recent evidence that VHL loss, which is linked tightly to clear cell histology, also leads to c-MET activation (13)(14)(15)(16). VHL loss in renal epithelial cells, but not in other cell types tested, leads to up-regulation of Cyclin D1 (17,18), which is a partner protein for Cdk6 and Cdk4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It nonetheless is intriguing that MET, CDK6, and MAP2K1 have been linked previously to kidney cancer biology. Germline MET mutations cause papillary renal carcinoma, and there is recent evidence that VHL loss, which is linked tightly to clear cell histology, also leads to c-MET activation (13)(14)(15)(16). VHL loss in renal epithelial cells, but not in other cell types tested, leads to up-regulation of Cyclin D1 (17,18), which is a partner protein for Cdk6 and Cdk4.…”
Section: Discussionmentioning
confidence: 99%
“…VHL loss leads, indirectly, to activation of kinases that are important for renal carcinoma tumorigenesis (reviewed in ref. 7), including kinases present within the tumor cells themselves, such as EGFR (11,12), c-Met (13)(14)(15)(16), and cyclin D1-associated kinases (17,18), and those associated with blood vessels, such as kinase insert domain receptor and platelet-derived growth factor receptor. Kidney cancer is refractory to most conventional chemotherapeutics and radiotherapy but often responds, at least temporarily, to drugs that inhibit kinase insert domain receptor.…”
mentioning
confidence: 99%
“…Aside from mediating HIF-a proteolysis, pVHL is involved in extracellular matrix (ECM) assembly matrix turnover, [42][43][44][45][46][47] the regulation of intracellular junctions, 48 NF-kB signaling, 49 the regulation of c-Met receptor responsiveness to hepatocyte growth factor (HGF) involving b-catenin 45,50 and the regulation of p53 transcriptional activity by suppressing Mdm2-mediated ubiquitination and nuclear export. 51 Furthermore, pVHL has been shown to regulate microtubule stability and cilia maintenance [52][53][54][55] and controls the activity of plant homeodomain protein Jade-1, 56,57 and atypical protein kinase C isoforms.…”
Section: Biological Functions Not Involving Hifmentioning
confidence: 99%
“…Similarly, Evans et al 107 demonstrated that knockdown of pVHL resulted in E-cadherin suppression via HIF-dependent induction of E2 box-dependent transcriptional repressors Snail and SIP1, and Krishnamachary et al 108 reported that HIF-1 activation in VHL-deficient cells downregulated Ecadherin, led to the loss of cell-cell adhesion and promoted epithelial to mesenchymal transition through the induction of transcriptional repressors TCF3, ZFHX1A and ZFHX1B/SIP1. Therefore, cellular changes, such as loss of intercellular junctions and epithelial de-differentiation involving HIFdependent as well as HIF-independent molecular pathways 48,[106][107][108] in addition to HIF-dependent and -independent alterations in p53 or NF-kB activity, 34,35,49,51 HGF signaling, 45,50,109 and modifications in ECM turnover and re-modeling [42][43][44][45][46][47] create the molecular environment for the development CC-RCC, which most likely requires additional genetic events. The importance of HIF activation in CC-RCC pathogenesis and growth is furthermore underscored by experimental and clinical studies, which demonstrated that inhibition of HIF-a translation by pharmacological targeting of mTOR correlated with reduced tumor growth, 110 and that increased expression of certain HIF target genes, such as CXCR4, as well as E-cadherin suppression was associated with disease progression.…”
Section: Pvhl and Renal Cell Cancermentioning
confidence: 99%
“…34 However, in contrast to adult sporadic clear cell renal cell carcinoma with a high percentage of VHL gene mutations and loss of heterozygosity of the VHL gene region, in renal cell carcinoma in young patients, VHL gene mutations are absent. 8 In this regard, the lack of b-catenin accumulation especially in the clear cell renal cell carcinomas in our current study is in accordance with our previous demonstration of the absence of VHL mutations and rarity of VHL alterations in renal cell carcinomas in young patients.…”
Section: Discussionmentioning
confidence: 97%